A new species of Orobanche (Orobanchaceae) from Turkey - Zare, Golshan (Phytotaxa, 2014)
Orobanche turcica (Orobanchaceae) is described as a new species from Turkey. The new species is a close relative of O. anatolica. Morphological differences of the new taxon from closely related species are discussed. A distribution map, illustration, as well as pollen and seed microphotographs of the species are provided.